A Design Solution for Efficient and Compact Electro-hydraulic Actuators. (2015) - Altare, Gabriele; Vacca, Andrea
Abstract: This paper presents and describes an innovative design solution for a compact Electro-Hydraulic Actuator (EHA). Although the current trend in many mobile applications is towards the use of Electro Mechanical Solutions (EMAS) instead of Hydraulic Actuation Systems (HAS), HEAs can actually represent the best technological compromise. In fact, EHAs can combine the power to weight ratio advantage of hydraulic technology with the versatility and ease of installation and control of electric technology. Compared to EMAS, which are often equipped with low efficient load holding mechanisms, EHAs can also offer superior energy efficiency. Moreover, the EHAs do not suffer of jamming problems, which make them a strong candidate to be employed in harsh environments. Applications of EHAs like the one proposed in this work include aircrafts, cargo and vehicle doors, hatches and landing gears. The system studied in this research is based on miniature bi-directional gear pump (from 0.13 cc/rev), specifically designed to maximize performance in terms of efficiency, noise emissions and durability for the reference application. This pump is used in a system layout architecture that includes built-in valves to allow a power on demand strategy control of a differential linear actuator. In particular, a novel pressure compensation system was formulated to minimize power losses associated with the internal lubricating gaps in the whole field of operation. The paper details the numerical modelling of the system, showing also results which describe its main features of operation. Advantages in terms of energy consumption, with respect to a more common configuration of EHA are also discussed.